Indonesia's Role in Maximising the Benefits of Foreign Investment for the Community Through Regulation of Entry Policies - Daniel Manalu, Kevin (SEAN Institute, 2025)
Indonesia, as one of the most populous countries in the world, faces the challenge of maximising the potential of its natural and human resources through foreign direct investment (FDI) activities. This study uses a normative legal method with a literature review approach to analyse how Indonesia, through its sovereignty, regulates entry in FDI to ensure economic growth and public welfare. The results of the study show that Indonesia has established a relatively comprehensive regulatory framework through Law No. 25 of 2007 on Investment, which includes guarantees against takeovers, dispute resolution mechanisms, tax and non-tax incentives, investment screening, local collaboration requirements, environmental protection, and provisions on local equity. These regulations have proven to play a role in minimising the risk of economic dependence, preventing the exploitation of natural resources, and strengthening the country's legal position in negotiations with foreign investors. This study found that Indonesia has succeeded in maximising the benefits of FDI, particularly through job creation, improving the competence of the local workforce through training, and technology transfer from foreign companies. However, the effectiveness of the policy is still influenced by implementation challenges such as licensing bureaucracy and legal certainty. This study concludes that regulations that balance investor protection and national interests are key to ensuring that FDI generates optimal benefits for the community. Recommendations are directed at strengthening investment governance, improving environmental sustainability standards, and harmonising central and regional regulations to create a more stable and inclusive investment climate.